COVID-19 and the finance-economic growth nexus in Kenya - Benjamin O. Maturu (Kenya Bankers Association (KBA), 2022)
We empirically re-examine the finance-economic growth nexus within the context of the COVID-19 pandemic using a financial intermediation model build upon the McKinnonShaw financial repression theory. The study findings show that there is a vicious circle of finance and economic growth which is exacerbated by McKinnon-Shaw-like financial repression. The COVID-19 pandemic labour supply shock adversely affects the human capital depreciation rate which in turn adversely affects the employment level in the economy and economic growth thereby compounding the vicious circle. Since the vicious circle cannot resolve itself, using appropriate socio-economic policies to break it is necessary. The authorities must however contend with the observed partial ineffectiveness of fiscal and monetary policies.
Keywords: 330